(untitled) (Fiep Bulletin - online, 2015)
In the Style of the Lingiads held in 1939 and 1949 the Federation Internationale de Gymnastique (FIG) decided to hold every fourth year a similar gymnastic Festival, which received the name “gymnaestrada”.